PENGARUH BRAND, INTERNET PROMOTION DAN RELATIONSHIP MARKETING TERHADAP LOYALITAS DISTRIBUTOR PADA PT.EKOSJAYA ABADI LESTARI DI SIDOARJO - Rosa Tuwi Suryani; Slamet Harjatno (Research Parks Publishers, 2020)
The purpose of this research is to know the influence of brand, internet promotion and relationship marketing to distributor loyalty on PT.Ekosjaya Abadi Lestari, either partially or simultaneously.The research uses a quantitative approach. The research method used is non probability sampling with simple purposive sampling technique. The instrument of this used questionnaire and analyzed using multiply linear regression. The result of hypothesis tesiting shows that simultaneously brand variable, internet promotion, and relationship marketing have a significant effect on distributor loyalty. Partially on brand variable has no significant effect on distributor loyalty, partially internet promotion variable has no significant effect on distributor loyalty, and partially relationship marketing variable significant influence on distributor loyalty. Among the variables affecting distributor loyalty, relationship marketing variable has the most significant influence on distributor loyalty